(untitled) (Panacea Journal of Medical Sciences, 2024)
Background: Bone marrow study is of fundamental importance in most haematological disorders including haematological malignancies, carried out to permit cytological assessment and for other specialized investigations. Trephine biopsy gives histological details of marrow including cellularity, fibrosis and reveals the causes of dry tap. Finer cytomorphological details of marrow elements can be ascertained by the imprint smears from the biopsy material. Materials and Methods: A total of 50 cases of haematological malignancies of both sexes within the age group of 4-82 years, were studied by cross sectional, descriptive study. Smears and biopsy sections were stained with routine and special stains. Bone marrow reticulin status was noted. The bone marrow aspiration results were correlated with the trephine biopsy reports and analyzed with standard statistical methods. Results: Out of 50 cases, diagnostic bone marrow aspiration (BMA) and bone marrow trephine biopsy (BMTB) were done in 44 cases and trephine biopsy alone in rest of the 6 cases. Bone marrow aspiration was non-diagnostic in 1 case (due to focal involvement) and dry tap occurred in 5 cases. Total 21 cases of acute leukaemia, bone marrow aspiration alone could reach to the diagnosis in 17 (81%) cases. Single case of acute myelofibrosis was diagnosed only by bone marrow biopsy. Mild to moderate degree increase in reticulin fibrosis were noted in 18 (36%) cases. Conclusion: Bone marrow aspiration and bone marrow trephine biopsy act as a complementary to each other so far the diagnosis and management of hematologic malignancies are concerned.